Analisis Faktor Determinan Yang Berhubungan Dengan Kesembuhan Pada Pasien TB Paru di Puskesmas Rejotangan Kabupaten Tulungagung - Sholha, Hanny Atus; Tri Nataliswati; Marsaid, Marsaid; Sulastyawati, Sulastyawati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Objective: Pulmonary Tuberculosis is still a public health problem in many countries including Indonesia. The key to successful prevention of Pulmonary TB is the discovery of patients and treatment of patients until recovery. This study aims to identify determinant factors associated with the recovery of pulmonary TB patients at the Rejotangan Community Health Center, Tulungagung Regency. Methods: The research design used was quantitative with a cross sectional approach and analytic in nature. The study population was 47 patients, with a sample of 36 respondents selected by purposive sampling. The instrument used was a questionnaire. Data analysis using the spearman test with a significance level of <0.05. Results: showed that, there was no relationship between age and recovery of pulmonary TB, no relationship between gender and recovery of pulmonary TB, no relationship between nutritional status and recovery of pulmonary TB patients, there was a relationship between knowledge and recovery of pulmonary TB patients, there was a relationship between treatment compliance and recovery of pulmonary TB patients, there was a relationship between the presence or absence of PMO with the recovery of pulmonary TB patients. The results of the spearman test showed a significance value on knowledge (p value = 0.001), treatment compliance (p value = 0.006), PMO (p value = 0.002) which means there is a relationship with the recovery of pulmonary TB and the most dominant factor is the knowledge factor with strength (-0.517) Conclusion: Spearman's test results showed an association between knowledge, medication adherence, and the presence or absence of PMO with TB cure. It is expected that patients can maintain knowledge about compliance in treatment according to the rules in order to avoid failure. Factor, Recovery, Pulmonary TB